Accurate multiconfiguration calculations of energy levels, lifetimes, and transition rates for Ge XIX. (October 2021) - Hu, Feng; Sun, Yan; Mei, Maofei; Pan, Yuewu; Wu, Miao; Liu, Hao
Highlights: Transition properties are reported for electric dipole, electric quadrupole, magnetic dipole and magnetic quadrupole transitions. Electron correlation and quantum electrodynamic (QED) effects in multi-valence electron systems are discussed. The accuracy of parameters is estimated with different methods. Abstract: Energy levels, radiative rates and lifetimes for electric-dipole (E1), electric-quadrupole (E2), magnetic-dipole (M1), magnetic-quadrupole (M2) transitions among the lowest 97 levels belonging to the 3s 2 3p 2, 3s3p 3, 3s 2 3p3d, 3s3p 2 3d, 3s 2 3d 2, and 3p 4 configurations in silicon-like Ge XIX have been calculated through Multiconfiguration Dirac-Hartree-Fock method. High-accuracy calculations have been performed with accurate treatment of relativity, electron correlation, and quantum electrodynamic effects, as well as inter-electron correlation. The calculated energy levels are in excellent agreement with available experimental data. The present results are reported as benchmarks for future calculations and measurements.